Pendidikan Kesehatan Tentang Pola Asuh Orang Tua Dalam Pembentukan Kemandirian Anak Usia Dini (4-6 Tahun) - Yessy Nur Endah Sary; Tri Iriyani; Nova Hikmawati; Homsiatur Rohmatin; Iit Ermawati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The parenting style provided by a child's parents influences the quality of their life, thereby enabling them to grow into socially mature individuals. Parental parenting styles have a significant influence on the lives of their children. The development of independence is an important characteristic that prepares young people for their future lives. The Community Partnership Program (PKM) this time aims to provide knowledge about childcare practices to parents who have young children (aged 4-6 years). PKM events were attended by 52 persons. The PKM team's health education for parents of early childhood children (4-6 years) through question and answer lectures was shown to be effective in increasing parents' knowledge about parenting patterns, factors that influence the success of parenting patterns, independence formation, and other factors that influence the success of independence.